Ideology on Children Formula Milk Television Commercials - dewi, kumala (Institut Seni Indonesia Denpasar, 2024)
Television advertising for children's formula milk is also a text produced from a certain ideological point of view, in the sense that advertising not only functions as a marketing medium for dairy products but also conveys ideology that can influence the mindset and decisions of the audience. This study focuses on analyzing the ideology behind television commercials for children's formula milk. The research aims to find out and provide an explanation of ideology in television commercials for children's formula milk. The method in this research is qualitative, with a textual analysis approach. The primary data is in the form of recordings of ten advertisements for formula milk products aired by several Indonesian national television stations. Secondary data was obtained through observation, literature study, online data searches, and questionnaires on the public as television viewers/consumers/parents. The results of the study show that the ideology behind the ten television advertisements for children's formula milk includes the ideology of idealism and consumerism.